Allium sativum L.: Therapeutic uses and pharmacological properties - Sunvej Choudhary; Mohd Ubed Noor; Md Sadique Hussain; Mudita Mishra; Swati Tyagi (Biogenesis: Jurnal Ilmiah Biologi, 2022)
Garlic (Allium sativum L.) is known as bulb vegetable or spice that utilized as herb and flavoring agent in food in many different countries. These herbs contain biologically active components that contribute to their pharmacological properties, which have been used medicinally for over 5000 years. Allium species have been shown to help reduce the development of tumors, anticancer, cardiovascular disease, aging process, infections, antiallergy, and antibiotic properties. The pharmacological activities of Allium species, both cultivated and wild, were examined in this work. This study implemented a literary analysis of the various pharmacological activities of A. sativum. The data was collected from reputable journals and electronic database, then analyzed using pictures and described qualitatively. Numerous studies have praised the chemical components of garlic for their use in the treatment of Alzheimer's disease, cardiovascular disease, cancer, diabetes, nephroprotection, atherosclerosis, osteoporosis, and wound healing. As a result, this manuscript is expected to inform and inspire researchers about the medicinal value of garlic.